Rancang Bangun Smart Controller untuk Tanaman Anggur di Greenhouse Menggunakan Modul Long Range (LoRa) - Mohammad Alif Budiman; Vania Reviana; Viving Frendiana (Politeknik Negeri Jakarta, 2022)
Grapes are one of the plants cultivated by the Duren Tiga greenhouse. Growing grapes requires soil that is not too wet, a temperature that is not too hot, and soil pH that is suitable are needed, so a smart greenhouse is needed to help monitor and irrigate the grapes. In this paper, a design of a smart controller using a Long Range (LoRa) module for a smart greenhouse system is presented. The system uses a DHT11 temperature sensor, a soil moisture sensor as a soil humidity sensor, a soil pH sensor, and a BH1750 light intensity sensor. A LoRa module with a frequency of 922 MHz and an ESP32 NodeMCU as a microcontroller on the transmitter and receiver side are needed for data transmission. Testing results of the temperature sensor in both nodes showed very good accuracy with error values of 1.40 and 1.49. Testing results of the soil humidity sensor in both nodes also showed very good accuracy with error values of 1.97 and 2.36. Similarly, testing of the soil pH sensor in both nodes resulted in good accuracy with error values of 1.34 and 1.72. Testing of the BH1750 light intensity sensor also showed good accuracy with error values of 4.13 and 5.08. Testing of the LoRa module showed a range of 1.4 km with an RSSI of -109 dBm and an SNR of -9.5 dB, and data that can be received up to 10 packets with a throughput of 42.67 bps, which is considered sufficient.